THE ROLE OF GAME-BASED LEARNING IN EXPANDING ENGLISH VOCABULARY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
:This article examines the role of game-based learning in expanding English vocabulary among language learners. Vocabulary acquisition is a fundamental component of language proficiency, and innovative teaching methods are increasingly being employed to enhance students' engagement and learning outcomes. Game-based learning integrates educational content with interactive and enjoyable activities, creating a motivating environment for vocabulary development.
Keywords: Game-based learning, English vocabulary, language acquisition, vocabulary development, educational games, English language teaching, learner motivation, communicative competence.